Communicating Context to the Crowd for Complex Writing Tasks - Salehi, Niloufar; Teevan, Jaime; Iqbal, Shamsi; Kamar, Ece (Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work (CSCW 2017), Portland, OR, 2017)
Crowd work is typically limited to simple, context-free tasks because they are easy to describe and understand. In contrast, complex tasks require communication between the requester and workers to achieve mutual understanding, which can be more work than it is worth. This paper explores the notion of structured communication: using structured microtasks to support communication in the domain of complex writing. Our studies compare a variety of communication mechanisms with respect to the costs to the requester in providing information and the value of that information to workers while performing the task. We find that different mechanisms are effective at different stages of writing. For early drafts, asking the requester to state the biggest problem in the current write-up is valuable and low cost, while later it is more useful for the worker if the requester highlights the text that needs to be improved. These findings can be used to enable richer, more interactive crowd work than what currently seems possible.We incorporate the findings in a workflow for crowdsourcing written content using appropriately timed mechanisms for communicating with the crowd.
Honorable Mention